Acute Cervical Disk Herniation Resulting in Sudden and Severe Neurologic Deterioration: A Case Series - Harel, Ran; Knoller, Nachshon (The Surgery Journal, 2016)
Objective Nontraumatic acute cervical disk herniation resulting in acute severe neurologic deficit is a rare entity described in a limited number of case reports. We describe the management and outcome in patients presenting with severe neurologic deterioration caused by acutely herniated cervical disks.Methods Four patients (mean age 39.5 years) presented to our tertiary care academic medical center from September 2012 to September 2013 with severe progressive neurologic deficits due to cervical disk herniation and were included in the series. Patients' surgical, medical, and imaging records were retrospectively reviewed under an Institutional Review Board waiver of informed consent.Results Patients in the series presented with acute neurologic deterioration, including paraparesis, Brown-Séquard syndrome, or quadriparesis deteriorating to quadriplegia. Emergent magnetic resonance imaging (MRI) scans and emergent decompression and fusion for acute soft disk herniation were performed in all cases. All patients recovered to excellent functional status with Frankel score improvement from B (one patient)/C (three patients) to E (three patients)/D (one patient).Conclusions Acute cervical disk herniation with acute neurologic deterioration is a medical emergency necessitating emergent MRI and surgical decompression. Clinical presentation varies. In patients with rapid-onset neurologic deterioration, a high level of suspicion for this rare entity is indicated.
Keywords: acute cervical herniated disk; acute neurologic deterioration; Brown-Séquard syndrome; cervical myelopathy; anterior cervical approach